2017
DOI: 10.22190/teme1604383s
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Leadership Styles in Serbian Organizations: Gender Influence/Анализа Лидерских Стилова У Српским Организацијама: Утицај Пола

Abstract: The objective of this study is to explore the role and relevance of leaders’ gender in their choice of dominant leadership style in Serbian companies and institutions. The categories we use in our research are based on the two most popular classifications of leadership styles, established in Iowa and Ohio studies (which identified authoritarian, democratic and laissez-faire style and task-oriented or relationship-oriented leadership style respectively). For data collection we used a 31-statement questionnaire,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…This is why the results cannot be predicted solely on the basis of the leadership style, but it is important to be familiar with the situational variables, too [15]. Besides, the leadership style depends on the staff's personal characteristics and abilities, on the elements of social surroundings and business environment, as well as other cultural, ethnical and historical aspects, too [39].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…This is why the results cannot be predicted solely on the basis of the leadership style, but it is important to be familiar with the situational variables, too [15]. Besides, the leadership style depends on the staff's personal characteristics and abilities, on the elements of social surroundings and business environment, as well as other cultural, ethnical and historical aspects, too [39].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Simic, Kezic, and Ristic (2017) [16] observed connection of the motivational structure with the quality of the relationship between leader and employees. Stojanovic-Aleksic, Stamenkovic, and Milanovic (2016) [18] investigated the relationship between gender leadership and leadership style applied by the leader and concluded that women leaders are more taskoriented and implement an authoritarian leadership style while men choose democratic leadership styles. Stojanovic-Aleksic and Zivkovic (2015) [17] conducted research on 38 Serbian companies and singled out the most important characteristics of leaders that form the basis of their power and that influence the formation of leadership skills.…”
mentioning
confidence: 99%